2015
DOI: 10.1016/j.jobaz.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of cardiac sarcoplasmic reticulum and sarcolemma in the ventricle of catfish (Clarias gariepinus)

Abstract: The present study was undertaken to examine the relative contribution of the SR-Ca 2+ release and sarcolemmal Ca 2+ channels in developing the cardiac force at two different temperatures (20 and 30°C) in the catfish (Clarias gariepinus).The sarcolemmal Ca 2+ contribution of activator Ca 2+ was greater at a test temperature of 30°C as assessed by verapamil. Whereas the SR-Ca 2+ contribution was higher at 20 and 30°C and a frequency rate of 0.2 and 0.4 Hz as assessed by caffeine and adrenaline, respectively. Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Our results also found that the strength of muscle contractions increases with decreases in temperature, saturating at 17-18°C. In addition, to the effects on axonal conduction properties, temperature may also affect multiple aspects of muscle contraction from membrane excitation (Vornanen, 2016), Ca 2+- dynamics from the SR (Abu-Amra et al, 2015; Shiels et al, 2002), Ca 2+ -dependent contraction activation (Ranatunga, 2018), and mechanisms of cross-bridge cycling (Wang and Kawai, 2001). While effects of temperature on synaptic efficacy appear to directly translate to the excitation-contraction coupling machinery, it is possible that temperature is also affecting multiple aspects of muscle biology.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also found that the strength of muscle contractions increases with decreases in temperature, saturating at 17-18°C. In addition, to the effects on axonal conduction properties, temperature may also affect multiple aspects of muscle contraction from membrane excitation (Vornanen, 2016), Ca 2+- dynamics from the SR (Abu-Amra et al, 2015; Shiels et al, 2002), Ca 2+ -dependent contraction activation (Ranatunga, 2018), and mechanisms of cross-bridge cycling (Wang and Kawai, 2001). While effects of temperature on synaptic efficacy appear to directly translate to the excitation-contraction coupling machinery, it is possible that temperature is also affecting multiple aspects of muscle biology.…”
Section: Discussionmentioning
confidence: 99%
“…Dugyala and Sharma (1996), Batey and Wang (2002) and Miao et al (2016) claimed that cellular components of the immune system which produce various cytokines play a key role in host resistance against intoxicating inflammatory actions. The tested isolated snake venom peptide BPF (GII 2 ) (ACE inhibitor) that potentiates the endogenous BK via activation of B 2 receptors; significantly increased the cytokine IL-1β against induced aflatoxicosis (Murakami et al 1997;Fernandes et al 2001;Abu-Amra et al 2015). The authors recorded a profound cell signalling that initiated gene expression for TNFα, phospho-lipase A 2 and other pro-inflammatory immune response by such activated bradykinin.…”
Section: Discussionmentioning
confidence: 99%